Synthesis and antiparkinsonian activity of nanocomposite of chitosan-tripolyphosphate-Mucuna pruriens L extract (CS-TPP-MP) - Sardjono, R. E.; Fauziyah, A. N.; Puspitasari, M. D.; Musthapa, I.; Khoerunnisa, F.; Azzahra, G. N.; R., Mamat; Erdiwansyah, . (IOP Publishing, 2020)
Mucuna pruriens L. (MP) has antiparkinsonian activity because it contains levodopa that acts as a dopamine precursor and plays a role to stimulate dopaminergic receptors in Parkinson's sufferers. The therapeutic efficacy of MP extract can be improved by using a nano drug carrier system, such as chitosan-tripolyphosphate (CS-TPP). This study aims to synthesize, characterize, and evaluate antiparkinsonian activity of chitosan-tripolyphosphate-MP extract (CS-TPP-MP) nanocomposite in mice. MP seed powder was extracted by maceration method using water-ethanol (1:1) by adding citric acid until it reached pH 3. The CS-TPP-MP nanocomposite was synthesized by using ionic gelation method with variations in reactant composition and reaction time. The CS-TPP-MP nanocomposite was characterized by Scanning Electron Microscopy-Energy Dispersive X-ray (SEM-EDX), X-Ray Diffraction (XRD) and Fourier-Transform Infrared (FTIR) Spectroscopy. Catalepsy test was performed to find the antiparkinsonian activity level of CS-TPP-MP nanocomposite at doses of 5, 10, 15, 20, and 25 mg/kg body weight. Based on the results of CS-TPP-MP synthesis, it was found that the reactant composition (CS-TPP:MP) of 1:3 with reaction time of 20 minutes produced the highest yield (14.21%.) SEM-EDX characterization showed that the morphology of CS-TPP-MP nanocomposite was predominantly spherical and the size was approximately 120-170 nm with a composition of C = 55.43%, O = 30.46%, N = 13.46%, P = 0.44%. XRD diffractogram showed that CS-TPP-MP nanocomposite has amorphous structure. FTIR analysis showed the appearance of absorption at wavelength of 1643.35 cm−1 which proved the interaction between the primary amine group of chitosan and the carbonyl group of EMP. Catalepsy test demonstrated that CS-TPP-MP nanocomposite at the doses of 5, 10, 15, 20, and 25 mg/kg body weight could reduce catalepsy symptoms in mice significantly, and the best dosage was 20 mg/kg body weight.